Productivity of Textile Industry and Textile Products in Central Java - Prasetyo, P. Eko (Universitas Negeri Semarang, 2017)
This article aims at examining further the importance of productivity and effectiveness of product development in textile industry and textile products (TPT industry) in Central Java. The productivity analysis method uses the American Productivity Center (APC) model and the Mundel model. The method of analyzing the measurement of the effectiveness of new product development uses New Product Index (NPI), Feature Function Index (FFI), and Time to Market Index (TMI). Data input is used for the purposes of this analysis, especially input of labors, capital, materials and energy, and data output of production of the TPT industry studied. The result of research shows that based on productivity analysis both with APC and Mundel methods, the productivity decreased except only in the Capital input variable which productivity level did not decrease. Based on the Mundel model, in more detail the decrease in productivity levels occurs in workers > + 1 Foreman, sales worker, production worker, and manager worker. Furthermore, the new product development is also not effective yet, and the best strategy to be chosen in developing new products in new markets is diversification strategy. The implication of this research is that the TPT Industry in Central Java still has to continuously improve its productivity and improve the development of new products effectively using diversification strategy.This article aims at examining further the importance of productivity and effectiveness of product development in textile industry and textile products (TPT industry) in Central Java. The productivity analysis method uses the American Productivity Center (APC) model and the Mundel model. The method of analyzing the measurement of the effectiveness of new product development uses New Product Index (NPI), Feature Function Index (FFI), and Time to Market Index (TMI). Data input is used for the purposes of this analysis, especially input of labors, capital, materials and energy, and data output of production of the TPT industry studied. The result of research shows that based on productivity analysis both with APC and Mundel methods, the productivity decreased except only in the Capital input variable which productivity level did not decrease. Based on the Mundel model, in more detail the decrease in productivity levels occurs in workers > + 1 Foreman, sales worker, production worker, and manager worker. Furthermore, the new product development is also not effective yet, and the best strategy to be chosen in developing new products in new markets is diversification strategy. The implication of this research is that the TPT Industry in Central Java still has to continuously improve its productivity and improve the development of new products effectively using diversification strategy.